IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN: STUDI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN BUTON TENGAH - Abdullah; Syamsul Alam; Tora Akadira (Journal Publicuho, 2025)
The success of information technology policy implementation is influenced by implementation fidelity, which includes compliance, exposure, responsiveness, and system quality. This study examines the level of implementation of the Personnel Management Information System (SIMPEG) at the Education and Culture Office of Central Buton Regency, using this framework. Using a descriptive quantitative survey method, data were collected through questionnaires from SIMPEG users. The results indicate that the SIMPEG implementation is at a moderate level, facing challenges such as inconsistent application of procedures, incomplete user understanding, limited user engagement, and system quality that requires improvement. These findings underscore the need to strengthen human resource capacity, socialisation, and training to ensure effective digital transformation of personnel management. The implementation fidelity approach provides a systematic evaluation framework that helps identify obstacles and opportunities in regional government digitalisation.